Insights on the Fates of Diarylamine Radical-Trapping Antioxidants During Inhibited Autoxidations Using Isotopically-Enriched Compounds - Penner, Neill (Université d'Ottawa / University of Ottawa, 2021)
The oxidative degradation of organic materials typically operates through a radical-mediated chain mechanism known as autoxidation; a process that has severe consequences in both biological settings (i.e. accumulation of lipid peroxides) and non-living substrates (i.e. breakdown of petroleum-derived materials, such as lubricants/oils, plastics, polymers, rubbers, etc.). However, autoxidation can be retarded by radical-trapping antioxidants (RTAs); chemical species that capture chain-carrying radicals to break the chain of oxidation. A particular class of RTA, diarylamines, have proven especially effective at elevated temperatures due to a purported catalytic mechanism of inhibiting autoxidation, and thus, have found significant use as protective agents in engine lubricant oils. However, the current diarylamine technology struggles to manage the increased oxidative stress placed on it by modern internal combustion engines (ICEs), which burn fuel at higher temperatures in order to meet emission standards. Designing superior diarylamines is not straightforward, however, as the mechanisms by which they are forced from their catalytic cycle are not well understood. Herein, we report our investigations into the fate of an industrially-representative, isotopically-enriched diarylamine during hydrocarbon autoxidation at elevated temperatures using a novel 2D 1H – 15N heteronuclear multiple bond correlation (HMBC) spectroscopic technique. Synthesis of a small scope of oxidation products allowed for the identification of a previously unreported product of diarylamine autoxidation. Additionally, a consistent pattern of diarylamine speciation under varying conditions was observed spectroscopically. Use of the HMBC technique also confirmed previous reports of the regenerative ability of the diarylamine and the intermediates of its purported catalytic cycle. Quantification studies using ultra performance liquid chromatography (UPLC) during the early stages of autoxidation provided insight into the formation of initial diarylaminic intermediates. Additionally, we examined the fate of the diarylamine during autoxidations in the presence of nitrogen oxides (NOx), which are found in the blow-by gas of ICEs and have been shown to exacerbate hydrocarbon autoxidation. The performance of diarylamine was drastically reduced under such conditions, and HMBC spectroscopy illustrated its rapid conversion to a number of intermediates. The most prominent two intermediates were identified as mono- and di-nitrated analogues of the original diarylamine, and were demonstrated to possess no RTA activity; regardless of temperature or substrate. HMBC spectroscopy also illustrated the differences in product distribution under each set of conditions.
Keywords: diarylamine; antioxidant; autoxidation; radical; hydrocarbon; HMBC